2010
DOI: 10.1111/j.1365-263x.2010.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro alterations in dental enamel exposed to acidic medicines

Abstract: Dimetapp(®) (lowest pH and viscosity) and deionized water (control) showed the most pronounced erosive patterns. Klaricid(®) (highest pH and viscosity) presented an in vitro protective effect against acid attacks perhaps due to its mineral content and viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 32 publications
6
51
1
7
Order By: Relevance
“…Other in vitro studies have also demonstrated that Claritin® may reduce enamel hardness (18)(19)(20) and increase surface roughness (17). In the present study, the varnishes were applied once and removed after 6 h of application to simulate the clinical condition, since the emphasis was allowing the chemical effect of the varnish components, rather than the mechanical protection.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies have also demonstrated that Claritin® may reduce enamel hardness (18)(19)(20) and increase surface roughness (17). In the present study, the varnishes were applied once and removed after 6 h of application to simulate the clinical condition, since the emphasis was allowing the chemical effect of the varnish components, rather than the mechanical protection.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro researches reported that medications can affect enamel hardness, and cause morphological and roughness alterations (5,9). Nevertheless, the results of these studies are limited to a small number of medicines, and the literature is scarce of articles that investigate the effects of medications on permanent and deciduous tooth enamel (9).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results of these studies are limited to a small number of medicines, and the literature is scarce of articles that investigate the effects of medications on permanent and deciduous tooth enamel (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valinoti et al 13) told that bovine enamel exposed to 3 kinds of children's syrups demonstrated erosive pattern by means of a scanning electron microscope. In addition, Sunitha et al 14) said inappropriate use of liquid medicines would have enormous potential to induce dental caries as syrups such as antipyretic·analgesic medicines, cough syrup with 10% of sucrose made experimental plaque's pH lower.…”
Section: Introductionmentioning
confidence: 99%